The Histadrut - Histadruth. General Federation of Jewish Labour in Palestine (Tel-Aviv : Histadrut, 1955)
Bibliotheek Camille Huysmans
Engels
Brochure
Keywords: joodse arbeidersbeweging; vakbonden; Israël